História natural das serpentes de uma área do Pampa brasileiro - Rosa, Conrado Mario da (2019)
Natural history studies of snake communities contribute both to increasing knowledge about the specific taxa biology and to elucidating interspecific relationships present in the community. Although the Brazilian Pampa possesses a high richness of snake species, this biome is still little studied in questions about the natural history of snakes, especially in the region between Brazil and Uruguay border. Considering the need to build knowledge about ophidiofauna of Pampa, we present richness pattern data on the distribution and abundance of community of snakes in an area of the Pampa biome. In addition, we report natural history aspects of species, especially for Thamnodynastes strigatus (Günther, 1858), describing hunting strategies, habitat use and activity patterns. We collected data from August 2017 to July 2018, in 11 monthly samples. For community data collection, we used the sampling methods: Active Search (BA), Occasional Encounters (EO) and Traps of interception and fall (PIT), and for meeting and monitoring of T. strigatus we used only BA. For the community, we performed 315 observations of 14 snake species, distributed in 12 genera and grouped into 5 families. The abundance of exposed snakes responded positively to the increase in the monthly average temperature. The most abundant snake was Epictia munoai (Orejas-Miranda, 1961), accounting for 38% of the records and the most frequent snakes were Erythrolamprus almadensis (Wagler, 1824) and Bothrops pubescens (Cope, 1870), recorded in 90% of the samples. In addition, we performed specific natural history observations of the snakes found, including data on habitat use, diet, reproductive period, individuals’ body size and defensive behaviors. For the natural history of Thamnodynastes strigatus (N = 74 individuals), we observed that this population, unlike the known for the species, is composed by ambush foragers specialists in fish predation. Besides, on two occasions we observed the lingual luring behavior for fish attraction, and we also provided additional data on habitat activity and use for this snake.